Recent Clinical Techniques, Results, and Research in Wounds - Gül, Vahit Onur; Destek, Sabahattin; DESTEK, SABAHATTİN; Ahioğlu, Serkan (My University, 2017)
Pilonidal sinus is a common disease of the sacrococcygeal area. Although many surgical treatment methods have been described, there is no ideal treatment, owing to the high recurrence rates, and available surgical techniques are still subject to debate. The existing treatment methods range from complete and large excision with or without wound closure to curettage of the sinus with a brush. Because of the high recurrence rates, pilonidal sinus can become a chronic and complicated disease, particularly when it is in the intergluteal area. Sometimes it may fistulize to the gluteal area, with secondary orifices opening to this region. In recent years, minimally invasive surgical techniques have become increasingly common in parallel with increasing experience and development of new instruments. When compared with large excisions, limited excision of the pilonidal sinus tract (fistula) may be a better treatment option regarding healing time and patient comfort. In this section, we explain why limited excision is a good treatment option not only in simple pilonidal sinus cases but also in complicated cases with recurrence and fistulization.